IMPLEMENTASI SISTEM PERADILAN PIDANA ANAK DALAM RANGKA MEWUJUDKAN KEADILAN RESTORATIF - Kayus Kayowuan Lewoleba; Mulyadi Mulyadi (Jurnal Ilmiah Hospitality, 2023)
Children in Conflict with the Law (ABH) are part of the community who are powerless both physically, mentally and socially, so they need special attention in handling them. Children who are well protected create a quality generation, which is needed for the future of the nation. For reasons of physical, mental and social immaturity, children need special attention and guidance, including legal protection both before and after birth. Children have the right to special protection and opportunities guaranteed by law and other means to grow and develop physically, mentally and socially. Protection of children is carried out in all aspects of life, special protection and obtaining opportunities guaranteed by law and other means, to grow and develop physically, mentally and socially. Protection of children is carried out in all aspects of life, including in this case in juvenile criminal justice. This research is a normative legal research that is strengthened by primary data to sharpen the analysis. The results show that the application of diversion in handling children in order to realize the concept of restorative justice or balanced justice between perpetrators and victims is a breakthrough in the juvenile criminal justice system. The results of the study show that the application of diversion in juvenile justice in order to realize restorative justice is the right step to prevent children from criminal justice which has the potential to rob children of independence. the application of punishment to children is the last option and is carried out in the shortest possible time